Structure and transition behavior of crosslinked poly(2-(2-methoxyethoxy) ethylmethacrylate-co-(ethyleneglycol) methacrylate) gel film on cellulosic-based flat substrate - Chen Yangyi; Su Tong; Zhou Shihang; Xie Chendi; Qi Huan; Cai Zaisheng; Chen Liqun (e-Polymers, 2024)
The structure and transition behavior of crosslinked thermo-responsive poly(2-(2-methoxyethoxy) ethylmethacrylate-co-(ethyleneglycol) methacrylate) (P(MEO2MA-co-EGMA360)) gel film on a flat cellulosic-based substrate were investigated. The regenerated cellulose (RC) film was prepared by spin-coating with trimethylsilyl cellulose (TMSC), followed by etching with hydrochloric acid vapor on a treated silicon wafer, then crosslinked polymer gel film was obtained by spin-coating, drying, and baking with a pre-crosslinked solution containing polymers. Fourier transform infrared spectroscopy, X-ray photoelectron spectrometer, and atomic force microscopy results show that a RC film with a thickness of 25 nm is generated in the upper layer of TMSC film on the silicon wafer. The cross-linking induces closer arrangement and hinders the extension of chain segments, leading to less prominent phase transition behaviors of polymer gel films. By quartz crystal microbalance measurement and 3D microscopes, a phase transition hysteresis is discovered, the hydrated and loose structure of crosslinked polymer gel film switches to dehydrated and compact structure in initial heating process, which subsequently recovers during the following cooling process. However, the degrees of rehydration and flexibility of film could not reach the initial value because of the insufficient transition time and steric hindrance caused by crosslinking.